Nanostructured KxNa1-xNbO3 hollow spheres as potential materials for the photocatalytic treatment of polluted water - Praxedes, Fabiano Rafael [UNESP]; Nobre, Marcos Augusto de Lima [UNESP]; Poon, Po Shan; Matos, Juan; Lanfredi, Silvania [UNESP] (Elsevier, 2021)
Potassium-sodium niobate-based hollows spheres were studied in the photocatalytic degradation of Basic Blue 41 dye in aqueous phase under UV irradiation. KxNa1-xNbO3 materials were prepared at 700oC by the spray pyrolysis method. Photocatalysts were characterized by XRD, SEM, TEM, N2 adsorption/desorption isotherms and FTIR. Different kinetic models of adsorption, direct photolysis, and photocatalytic degradation of the azo-dye were performed as a function of the pH of solution. The increase in potassium content is responsible of the distortion and polarization of the niobate structure promoting a decrease in the energy band-gap down to 3.01 eV for K0.5Na0.5NbO3. The photocatalytic activity observed on K0.5Na0.5NbO3 was up to 23 times higher than that on TiO2 in terms of the surface concentration of the azo-dye molecules adsorbed. A mechanism for the degradation of Basic Blue 41 azo-dye based on the reactive oxygen species detected by scavenger’s tests and mass-spectroscopy analysis was proposed.
Keywords: KxNa1-xNbO3 photocatalysts; Ultrasonic spray pyrolysis; Hollow spheres; Basic blue 41